Antara Ritual dan Realitas: Kritik Al-Qur’an Terhadap Kelalaian Shalat - Moh. Syifa’ Akmaluddin Bukhori; Evi Muzaiyidah Bukhori (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This paper examines the Qur’an’s critique of the phenomenon of neglecting prayer by addressing the theme “Between Ritual and Reality: The Qur’an’s Critique of Neglecting Prayer.” Drawing on Surah al-Ma’un, verses 4–7, this study highlights the tension between the outward ritual practice of prayer and the social and spiritual reality that should be reflected in it. This study employs a qualitative approach using a descriptive-comparative method, drawing on the interpretations of two exegetes: al-Qurt}ubi> in “Tafsi>r al-Ja>mi’ li Ah}ka>m al-Qur’a>n” and Sayyid Qut}b in “Fi> Z{ila>l al-Qur’a>n”. The findings indicate that the Qur’an’s criticism is not directed solely at those who abandon prayer, but also at those who perform it in a formalistic manner without fostering spiritual awareness or social impact. al-Qurt}ubi> emphasizes that neglect of prayer encompasses disregard for its prescribed times, pillars, and the perfection of the act of worship, which constitutes a major sin. Meanwhile, Sayyid Qut}b highlights the moral-social dimension, namely the attitude of showing off (riya’), the loss of sincerity, and indifference toward others as concrete manifestations of such negligence. Thus, prayer, from the Qur’an’s perspective, is not merely understood as a ritual act of worship but also as a manifestation of spiritual and social integrity. This critique emphasizes that the disconnect between worship and social behavior constitutes a form of negligence that leads to the threat of calamity.